On Queer Assemblages: An Overdue Conceptualization. - Hueso-Vasallo, Manuel (My University, 2024)
This paper examines the affinities between Assemblage Theory and Queer Studies by pointing out how both fields of research share a number of ‘points of contact’, both superficial and profound. It pays special attention to the controversial origins of both theories, as well as to their rejection of essentialism and binaries, and their shared concern with multiplicity and political activism. Furthermore, it addresses their practical and analytical benefits when considered together through an analysis of Justin Torres’s recent novel Blackouts (2023).
Keywords: Teoría queer; Torres, Justin (1980-) - Crítica e interpretación; Teoría crítica; Queer studies; Assemblage theory; Justin Torres; Bill Brown